IMPLEMENTASI PERMENKUMHAM NOMOR 6 TAHUN 2013 TENTANG TATA TERTIB LAPAS DAN RUTAN TERHADAP PELANGGARAN OLEH WARGA BINAAN PEMAYARAKATAN DI RUTAN KELAS IIB KRAKSAAN - Basri, Hasan (JUSTNESS - Jurnal Hukun dan Agama, 2024)
Abstract   The penitentiary institution or State Detention Center (Rutan) is an institution with all the risks of looking after convicts or those who are serving prison sentences. This research aims to describe the application of disciplinary punishments to correctional inmates who violate the rules and regulations at the Class IIB Kraksaan Detention Center according to Minister of Law and Human Rights Regulation Number 6 of 2013 concerning Rules for Prisons and Detention Centers. The second is to examine and analyze the obstacles faced by the Class IIB Kraksaan Detention Center in providing guidance to correctional inmates who are indisciplined for violations of rules and regulations. The method used in this research is empirical research. The results of the research show that the application of disciplinary law to correctional inmates is in accordance with Law Number 22 of 2022 concerning Corrections and Minister of Law and Human Rights Regulation Number 6 of 2013 concerning Regulations for Prisons and Detention Centers. Meanwhile, the obstacles faced in taking action are due to the existence of familial relationships between employees and inmates, the lack of personnel, the behavior and character of inmates who are not aware of the law.   Keywords : Implementation, Disciplinary Punishments, Community Inmates, Detention Centers